Chilean senior citizens in the 21st century: a polytologic approach - Morales Contreras, María Eugenia (Acta Bioethica, 2001)
Currently, Chile has a free market development model, which has been maintained within the last decade through some adjustments intended to correct different social imbalances. Capitalism without state intervention cannot be sustained in democratic countries. Old age and ageing are addressed within this context. The issue is approached from an individual and social angle, under a multidisciplinary point of view. The images, which present society has regarding old age, refer to cultural patterns which hardly recognize that ageing is a unavoidable situation for human beings. Ageing is perceived and transmitted as a painful situation, biased by images of old people: ill, disabled, suffering emotional disorders, and representing an emotional and economic burden on their families. The concept of "quality of life" considers subjectivity as an essential element, therefore expectations are above all individual. Likewise it has a multidimensional and complex character, produced by diversity. It is also a dynamic concept, as it varies with time. Groups in reduced social and economic conditions tend commonly to share their homes with their elders, being these not only their parents, but also relatives, or even some not related by kinship. Political participation is oriented to influence those decisions which compromise the destiny of the collectivity as a whole. The social participation concerns those closest to the development of the daily life of the individuals. Even though senior citizens constitute a relevant electoral market with growing importance, its role as political actors is still irrelevant.